Four new Megaselia species (Diptera: Phoridae) from aanimal carcasses in Bangi, Malaysia - Zuha, Raja Muhammad; Disney, R. Henry L. (Zootaxa, 2018)
Megaselia bangiensis Disney sp. nov., M. cumpapillarum Disney sp. nov., M. hyplongiseta Disney sp. nov. and M. selangorensis Disney sp. nov. were collected from rabbit carcasses placed in concealed environments in Bangi, Malaysia.